What Are Key Factors to Consider When Installing Large Butterfly Valves Belowground?. Issue 10 (1st October 2017) - Ballun, John V.; Holstrom, John R.
Abstract : When projects require direct buried installation of large butterfly valves, special installation factors must be considered to maintain valve integrity. This column reflects the views of the joint task force developing recommendations for improving industry and AWWA standards and manuals of practice to disseminate knowledge about this concern and identify potential solutions.